A agroindústria canavieira do Paraná pós-desregulamentação: uma abordagem neoschumpeteriana - Rissardi Júnior, Darcy Jacob (2005)
The study has as aim to analyse the main conditions of the evolution of the Paraná State sugar cane agroindustry after the sectorial deregulation according to the neoschumpeterian instrument The use of the neoschumpeterian approach through mainly Nelson and Winter?s Rosenberg?s Freeman?s Dosi?s and Cochrane?s studies are due to the fact that according to this group economic thought there is a competitive dynamics in which the innovation is a central differentiation element among the companies This study is configured as of qualitative nature and for the data collection in the surveys the questionnaire was used as an interrogation technique It must be emphasized the fact that the Paraná State companies which compose the sugar cane agro-industrial sector to be inserted since the sectorial deregulation occured in 1990 in the effective technological paradigm in the sector where it is necessary to be alert to the important attributes for the biggest sectorial competitiveness such as: bigger verification of costs; introduction of innovation in products and processes; and acquisition and construction of abilities and skills in the development of productive technological and organization qualifications The reasonable capacity of adaptation to the conditions of free competition in the Paraná State sugar cane agroindustries in the period of 1990 to 2005 investing in technological innovations of products and processes can be stood out There was in this way a technological heterogeneity where some move away because of the adoption of offensive technological strategies Other excellent results in percentile distribution of the searched companies answers were: the great impact caused by the occured technological innovations in the agricultural area overcoming in a significant way the industrial and administrative areas; and learning-by-interacting as a type of predominant learning in the Paraná State sugar cane agroindustry